PENDAMPINGAN BELAJAR MEMBACA AL–QUR’AN DENGAN ILMU TAJWID DI MAJELIS AL KAUTSAR DESA PANGABUAN KELURAHAN GUNUNG SUGIH KECAMATAN CIWANDAN KOTA CILEGON - Munawaroh, Munawaroh; Khodijah, Ina; Ningrum, Anggun Cahya; Sherlinda, Sherlinda; Nakhwah, Kamila Sari; Salmah, Ratu Ummu; Miftahurrohman, IIP; Rahmawati, Rosita (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Majelis Al Kautsar, located in Desa Pangabuan, Kecamatan Ciwandan, Cilegon City, serves as a center for religious activities. This majelis also functions as a place for religious education, particularly for teaching the Quran to children living in the surrounding area. However, a challenge that persists in Quranic education is the lack of deep understanding among children regarding the correct application of tajwid rules. Children attending the study sessions tend to recite the Arabic letters without correctly applying the rules of tajwid. This initiative aims to provide education on tajwid and proper Quranic pronunciation and reading according to tajwid rules. The method used in this tajwid training involves direct face-to-face teaching, where children at Majelis Al Kautsar receive structured theoretical and practical instruction. The results of this initiative indicate an improvement in the ability to read the Quran correctly in accordance with tajwid principles